PENGARUH KECERDASAN EMOSIONAL, KECERDASAN SPIRITUAL, DAN PERILAKU BELAJAR TERHADAP PEMAHAMAN AKUNTANSI DILIHAT DARI PERSPEKTIF GENDER (Studi pada Universitas Riau, Universitas Islam Riau, dan Universitas Islam Negeri Sultan Syarif Qasim II) - Aditya Trinovryan; Nur Azlina; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study examines the effect of Emotional Quotient, Spiritual Quotient, and Learning Behavior on Accounting Understanding be Observed from Gender Perspective. Population of this research is accounting college students in Riau Province. The sample used in this research was accounting college students on Riau University, Islamic Riau University, State Islamic University. Sample Selected by purpossive samping and data collected use questionnaires. By using simple linear regression, the result of study shows that Emotional Quotient have significant effect on Accounting Understanding sig by 0,000<0,05 , Spiritual Quotient have significant effect on Accounting Understanding sig by 0,032<0,05 , and Learning Behavior have significant effect on Accounting Understanding sig by 0,034<0,05 and be found the difference of Emotional Quotient between male and female gender sig by 0,001<0,05, Spiritual Quotient between male and female gender sig by 0,002<0,05, Learning Behavior between male and female gender sig by 0,001<0,05, and Accounting Understanding between male and female gender sig by 0,011<0,05.Keywords: Emotional Quotient, Spiritual Quotient, Learning Behavior, Accounting Understanding, and Gender